1977
DOI: 10.1177/000348947708600617
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological Observations on the Cochlear Changes in Otosclerosis

Abstract: Alterations in the dimensions of the basilar membrane and spiral ligament have been implicated in the pathogenesis of sensorineural hearing loss in otosclerosis. The histopathological findings in nineteen temporal bones with otosclerotic involvement of the cochlear endosteum are reviewed. Hyalinization and decrease in the width of the spiral ligament are the only consistent findings related to the otosclerotic focus in these temporal bones. The width of the basilar membrane is normal. The hair cell population … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1979
1979
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“… 6,8,38,41,42,44,48,49 Some investigators have observed a localized affect of otosclerotic endosteal involvement of the cochlea with atrophy of the adjacent stria vascularis 34,35,39,40,48,50 or hair cell and nerve fiber loss. 50 Others have observed a generalized affect on stria vascularis atrophy 46 and hair cell loss. 46,48 Both a localized and a generalized affect of otosclerotic endosteal involvement on the sensorineural structures are consistent with the theory that toxic substances generated by the otosclerotic focus diffuse into the perilymphatic fluid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 6,8,38,41,42,44,48,49 Some investigators have observed a localized affect of otosclerotic endosteal involvement of the cochlea with atrophy of the adjacent stria vascularis 34,35,39,40,48,50 or hair cell and nerve fiber loss. 50 Others have observed a generalized affect on stria vascularis atrophy 46 and hair cell loss. 46,48 Both a localized and a generalized affect of otosclerotic endosteal involvement on the sensorineural structures are consistent with the theory that toxic substances generated by the otosclerotic focus diffuse into the perilymphatic fluid.…”
Section: Discussionmentioning
confidence: 99%
“…Antoli‐Candela et al 46 measured the width of the basilar membrane and the spiral ligament in 17 temporal bones with otosclerotic involvement of the endosteum and 10 normal temporal bones. No difference in the width of the basilar membrane was observed between the two groups.…”
Section: Literature Reviewmentioning
confidence: 99%
“…postulated that this would be the result of the toxic actions of enzymes released from otosclerotic foci as will be described later in this paper. Another explanation suggests that hyalization of the spiral ligament due to otosclerotic foci is associated with sensorineural hearing loss 27‐29 …”
Section: Literature Studymentioning
confidence: 99%
“…Hyalinization of the spiral ligament adjacent to the otosclerotic foci has been shown to be associated with sensorineural hearing loss (Antoli-Candela et al 1977;Gussen 1975;Hinojosa and Marion 1987).…”
Section: Does Otosclerosis Present Only As a Conductive Hearing Loss?mentioning
confidence: 99%